Nitrogen nutrition and antioxidant metabolism in ammonium-tolerant and -sensitive plants - Domínguez-Valdivia, María Dolores (2011)
Ammonium nutrition is of interest as an alternative to that of using nitrate. However, the former has been reported as stressful to many plant species especially to some important crops, as most abiotic stresses may trigger oxidative imbalances in plants. In this work, we investigate the response of oxidative metabolism of two plant species, spinach (Spinacia oleracea L. cv. Gigante de invierno) and pea (Pisum sativum L. cv. Rondo), which have distinct tolerance to ammonium. Plants were grown in the presence of 1.5 and 3.0 mM N as ammonium and compared with equivalent nitrate nutrition. The antioxidant enzymes and metabolites as well as oxidative damage to proteins were determined. Protein and amino acid contents in both types of plants were also analysed. Ammonium nutrition in sensitive spinach or in the tolerant pea plants does not alter the redox status of ascorbate and glutathione or the phenolic contents, while no clear effect is seen in the antioxidant enzymes. The results showed that the stress originated from applying ammonium as the only N source is not an oxidative stress, independent of the ammonium tolerance of the plant species studied. Moreover, ammonium stress diminishes oxidative damage to proteins in the spinach plants. The data of the protein oxidation together with those from N metabolism highlight the relation between the stress induced by ammonium and an increased protein turnover.